Lidocaine Sensitizes the Cytotoxicity of Cisplatin in Breast Cancer Cells via Up-Regulation of RARβ2 and RASSF1A Demethylation - Li, Kehan (Int J Mol Sci, 2014)
It has been reported that lidocaine is toxic to various types of cells. And a recent study has confirmed that lidocaine exerts a demethylation effect and regulates the proliferation of human breast cancer cell lines. To recognize a potential anti-tumor effect of lidocaine, we evaluated the DNA demethylation by lidocaine in human breast cancer lines, MCF-7 and MDA-MB-231 cells, and determined the influence of demethylation on the toxicity to these cells of cisplatin, which is a commonly utilized anti-tumor agent for breast cancer. Results demonstrated that lidocaine promoted a significant global genomic demethylation, and particularly in the promoters of tumor suppressive genes (TSGs), RARβ2 and RASSF1A. Further, the lidocaine treatment increased cisplatin-induced apoptosis and enhanced cisplatin-induced cytotoxicity. The combined treatment with both lidocaine and cisplatin promoted a significantly higher level of MCF-7 cell apoptosis than singular lidocaine or cisplatin treatment. Moreover, the abrogation of RARβ2 or RASSF1A expression inhibited such apoptosis. In conclusion, the present study confirms the demethylation effect of lidocaine in breast cancer cells, and found that the demethylation of RARβ2 and RASSF1A sensitized the cytotoxicity of cisplatin in breast cancer cells.